Metabolism and Tissue Distribution of Chelerythrine and Effects of Macleaya Cordata Extracts on Liver NAD(P)H Quinone Oxidoreductase - Huang, Chong-Yin; Huang, Ya-Jun; Zhang, Zhuo-Yi; Liu, Yi-Song; Liu, Zhao-Ying (Frontiers in Veterinary Science, 2021)
Background Macleaya cordata (Willd.) (Papaveraceae) is listed as feed additives in animal production by the European Food Authority. Methods The metabolites of chelerythrine in rat in vitro and in vivo by rapid and accurate high-performance liquid chromatography/ quadrupole-time-of-flight mass spectrometry (HPLC/QqTOF-MS). Results Eight metabolites of chelerythrine were characterized by this approach in rat liver S9 and in vivo, respectively. The reduction of the iminium bond of chelerythrine and subsequent O-demethylation was the main metabolic pathway of chelerythrine in rat liver S9 while the reduction of the iminium bond of chelerythrine was the main metabolic pathway of chelerythrine in rat in vivo. After rats were intragastric administration. The low concentration residues of sanguinarine and chelerythrine in rat different tissues were found at 48 h after last dose, suggesting that the both two compounds could be widely distributed in tissues. The results also indicated XO, NQO1, NQO2 and carbonyl reductase are involved in chelerythrine reduction. Macleaya cordata extracts treated female and male rats, respectively, showed different responses, inhibiting NQO1 activity in males, but inducing NQO1 activity in females. And chelerythrine had a weak impact on NQO1 activity, but sanguinarine inhibited NQO1 activity Conclusion Collectively, the current study provided a reference for the clinical application and food safety evaluation of Macleaya cordata extract.